Geochemical and palaeontological characterization of a new K-Pg Boundary locality from the Northern branch of the Neo-Tethys: Mudurnu – Göynük Basin, NW Turkey. (January 2015) - Açıkalın, Sanem; Vellekoop, Johan; Ocakoğlu, Faruk; Yılmaz, İ. Ömer; Smit, Jan; Altıner, Sevinç Ö.; Goderis, Steven; Vonhof, Hubert; Speijer, Robert P.; Woelders, Lineke; Fornaciari, Eliana; Brinkhuis, Henk
Abstract: A Cretaceous-Paleogene (K-Pg) succession is studied in detail in the Mudurnu-Göynük basin in northwestern Turkey. To characterize the K-Pg transition in this basin, two stratigraphic sections were measured and sampled at high resolution: the Okçular and the Göynük North sections. These sections were analysed for siderophile trace elements, including Ir and other platinum group elements (PGE: Ru, Rh, Pd, Ir, Pt), bulk stable carbon isotopes, calcareous nannofossils, planktic foraminifera and organic-walled dinoflagellate cysts (dinocysts). In this basin, the upper Maastrichtian consists of monotonous grey mudstones, mostly intercalated with turbidites and the basal Danian is characterised by grey mudstones, that are overlain by a rhythmic alternation of limetones and mudstones. The K-Pg boundary is marked by a thin, reddish ejecta layer, characterized by an enrichment of PGE and an abrupt negative shift in bulk δ 13 C. This ejecta layer is followed by 15–17 cm of thick darker, clayey mudstone, the so-called boundary clay. The upper Maastrichtian to lower Danian interval displays a succession of biostratigraphic events, such as the globally recognized spike of the dinocyst taxon Manumiella druggii in the Maastrichtian, followed by the extinction of Cretaceous planktic foraminifera at the K-Pg boundary, and a subsequent rapid succession of First Occurrences (FOs) of dinocysts, such as Senoniasphaera inornata, Membranilarnacia ? tenella and Damassadinium californicum and planktic foraminifera, including Parvularugoglobigerina eugubina and Subbotina triloculinoides in the lower Danian. Overall the sedimentological and palaeontological data suggest that the studied sites in the Mudurnu-Göynük basin were deposited under normal marine conditions, likely in an outer neritic to upper bathyal environment. Our geochemical and biostratigraphic characterization of the K-Pg boundary transition in the Mudurnu-Göynük basin provides a new K-Pg boundary record in the Northern branch of the Neo-Tethys and allows a detailed comparison with K-Pg boundary sections worldwide.